Higher taxa as surrogates of species richness of spiders in insect-resistant transgenic rice - Lin, Sheng; You, Min-Sheng; Vasseur, Liette; Yang, Guang; Liu, Feng-Jing; Guo, Feng (Insect science, 2012)
Biodiversity assessments can often be time- and resource-consuming. Several alternative approaches have been proposed to reduce sampling efforts, including indicator taxa and surrogates. In this study, we examine the reliability of higher taxon surrogates to predict species richness in two experimental rice fields of Fujian Province, southeastern China during 2005 and 2009. Spider samples in transgenic and nontransgenie plots were collected using a suction sampler. Both the genus and family surrogates had significant and positive linear relationships with species richness in the transgenic and nontransgenic rice fields. The rice varieties did not significantly influence the linear relationships. Our findings suggest that higher-taxon surrogacy could be a useful alternative to complete species inventory for risk assessments of transgenic rice.